Facts, Values, and Methodology : A New Approach to Ethics - Steen, Wim J. van der, (Value Inquiry Book Series ;, 1995)
Science is not value-free and ethics is not fact-free. Science and ethics should be similar, but they are not. The author indicates how research in ethics is to change in the face of this. Ethicists should accommodate empirical work in their programs and they should take heed of methodologies developed in science and philosophy of science. They should abandon the search for a single overarching theory of morality. Controversies in ethics are often spurious for lack of articulate methodological key concepts. For example, disagreements over the value of general theories are misguided since disputants implicitly use different notions of generality and different notions of theory. An appropriate methodology does not suffice for the resolution of controversies but it is indispensable for consensus. The book argues these theses in a general way and applies them to the subject of egoism and altruism in ethics. Further case studies concern the environment and psychiatric disorders.